A light barricade for tailings recycling as cemented paste backfill. (20th February 2020) - Lu, Hongjian; Qi, Chongchong; Li, Chenghe; Gan, Deqing; Du, Yingnan; Li, Sheng
Abstract: The cemented paste backfill (CPB) technology that recycles waste tailings to fill underground voids is crucial for cleaner production of mineral resources. A main challenge in its application is the generally high cost and long time-period incurred to ensure the stability of the barricades (retaining wall structures). To circumvent these trends, a new light barricade with improved construction efficiency, mitigated material usage, and reduced operational cost is presented in this paper. The proposed barricade comprises recycled waste products from mining operations as main construction materials. These include rebar skeletons, mesh reinforcement, wood board, earthwork cloth, and steel support. The new barricade concept has been discussed in detail. This is followed by the description of an engineering application of the barricade in Shirengou Iron Mine (SIM). The backfill height in a single operation ( h ) and the distance from the barricade to the stope drawpoint ( l ) can be optimized using numerical simulations. These parameters were determined to be 1.5 m and 4–6 m, respectively, for SIM. The SIM implementation of the proposed barricade illustrates that it could reduce construction time from the 72 h for a brick barricade to 40 h, reuse steel pipes and mesh reinforcement for 6–8 cycles and wood board for 3–4 cycles, and decrease the barricade cost from 1050 RMB/m 3 to 727 RMB/m 3 . Therefore, the present study offers an efficient, reusable, and economical strategy for barricade construction that can be applied to the CPB practice in underground mines. Graphical abstract: Image 105494 Highlights: A light barricade is proposed for tailings recycling as cemented paste backfill. The structure, material and key construction technology are introduced. The required experiments and process parameters are introduced. Its capability is verified at an engineering case, the Shirengou Iron Mine (SIM). The proposed barricade is efficient, reusable and cost-effective.